Plastic policy hypocrisies: evaluating the efficacy of bans and alternatives in the Eastern Caribbean - Graham, Roxanne E. D. (Frontiers in Sustainability, 2024)
This study critically examines the socio-economic impacts and practical challenges of implementing plastic policies and regulations such as bans in Caribbean small island developing states (SIDS), within the broader context of global environmental efforts. By employing a mixedmethods approach, the research uses qualitative data from expert interviews from the Windward Islands in the south-east of the Caribbean, and on the ground observations and documentation of plastic and alternative usage in the island of Grenada. The findings highlight a significant 'plastic policy hypocrisy', where bans on single-use plastics exist alongside a heavy reliance on imported goods predominantly packaged in plastic. This contradiction points to a broader issue in environmental policymaking, where surface-level solutions like bans are employed without addressing underlying systemic challenges, such as inadequate recycling infrastructure or lack of export opportunities for recyclable materials. The research highlights how these policies, though well-intentioned, may fall short in practicality and global alignment. The study highlights the need for holistic, globally informed, and context-sensitive approaches to marine environmental related policies in Caribbean SIDS. Emphasizing the integration of ecological, economic, and cultural dimensions, it advocates for regional and international collaboration to enhance marine litter specifically plastic policy development and technical expertise.